O que funciona para melhorar a proficiência do aluno ? o impacto do programa de alfabetização na idade certa - PAIC e outros determinantes - Holanda, Ana Maria de Lima (2013)
This Study aims to analyze the impacts of the Literacy Program at Right Age (PAIC), and other variables that characterize the householders, schools and teachers, on the outcome of Proof Brazil in 2011 from students at 5th Grade of Elementary School that participated of this program in 2007 and 2008 (2nd year of Elementary School). For this we estimate two models using methods of OLS and SUR using municipal microdata from Proof Brazil and data from Brazilian Institute of Geography and Statistics (IBGE). Through a comparative analysis of the results we have found evidences supporting the hypothesis that the PAIC Program plays a role in the education of the children from the cities that have established the program, especially those whose mothers are less literate